The design of the buil ding for didactic in the tissue downtown Rzeszow - Rybka, Adam; Tylutki, Katarzyna (Видавництво Львівської політехніки, 2013)
Faculty of Arts, University of Rzeszow as a place where art is created, a kind of melting pot experiment and new ideas. Contact modernity and tradition, the continuous process of creation and development of thought interact not only in the same university. Contribute to society in the scale of the city, the region and the whole country. Ar t School is to help students develop their skills and knowledge, awareness of both their own individuality, and finding them as members of different groups in society. Among the objectives of arts education the emphasis is on creativity, often associated with its importance for innovat ion. The aim of the project was to create an architectural concept in software space – the building of the Fa culty of Arts, University of Rzeszow. The added value is to create new tissue cultural–entertainment in the city center of Rzeszow. The proposed facility is close to the existing perspective-traffic and diversifies the current development of this part of downtown Rzeszow. The source of inspiration for the form of the building was the composition of 1919 -"Lozenge: Color plans", Piet Mondrian, the Dutch painter, the greatest creator and pioneer of geometric abstraction in painting. The project refers to the land by the proportions of the building and the layout of its environment. Факультет мистецтв університету міста Жешув це місце, де мистецтво створюється, свого роду експериментально і з нових ідей. Зв'язок з сучасністю і традицією, безперервний процес створення і розвитку ідей взаємодіють не тільки в університеті. Внесок у розвиток суспільства в масштабах міста, регіону та країни в цілому. Художня школа має допомогти студентам розвивати свої навички і знання, зрозуміти і власну індивідуальність, і знайти їх в якості членів різних груп у суспільстві. Серед цілей мистецтва головним акцентом освіти є творчість, часто пов'язана з його важливістю для інновацій. Мета проекту полягала в розробц і концепції архітектурного простору програмного забезпечення – факультет мистецтв будівництва в університеті міста Жешув. До даної цінності можна також додати створення нових культурно–розважальних місць міста Жешув. Джерелом натхнення для вигляду будівлі являє собою композицію з 1919 р – "Lozenge: color plans", Piet'a Mondrian`a, голландського художника, найвідомішого творця і піонера геометричної абстракції в живописі. Проект відноситься до пропорції планування будівлі та його околиць.
Keywords: art; architectural design; building; downtown Rzeszow; мистецтво; архітектурне проектування; будівництво центру міста Жешув